BIOSURFACTANT PRODUCTION BY BACILLUS STRAINS RO7 AND R28 GROWN ON DIESEL - Ijah, U.J.J.; Olarinoye, R. (Malaysian Journal of Science, 2012)
Bacteria isolated from waste lubricating oil polluted soil were screened for biosurfactant production using haemolytic activity on blood agar, emulsifying activity and surface tension. Seventeen (45.95%) out of 37 isolates were heamolytic, indicating ability to produce biosurfactant. They were identified as species of Bacillus. Bacillus strains R07 and R28 exhibited maximum growth in diesel medium and formed less stable and stable emulsions, respectively. Based on these capabilities, the two strains were selected for biosurfactant production. Bacillus strain R28 had a higher emulsifying activity than R07 and was able to reduce the surface tension (ST) of diesel medium from 64 dynes/cm to 27 dynes/cm while R07 reduced the ST to 35 dynes/cm after 8days. R28 generated 0.6g/100ml of biosurfactant after 8days while R07 generated 0.4g/100ml over the same period. The biosurfactants produced by both strains contained substantial amount of phosphate and traces of protein but had no sugar. The biosurfactants were made up of 0.7% 1,2 diglycerides and 1.5% palmityl stearate for R07 and R28 respectively and were suspected to be phospholipids. The results obtained suggest that Bacillus strains R07 and R28 can produce biosurfactants that may be useful in the oil industry for enhanced oil recovery and bioremediation of oil spills. (Keywords: Biosurfactant, bacteria, bioremediation, hydrocarbons, phospholipids)